Src kinase as a potential therapeutic target in non‐alcoholic and alcoholic steatohepatitis. Issue 1 (20th February 2022) - Kurniawan, Dhadhang Wahyu; Booijink, Richell; Jajoriya, Arun Kumar; Dhawan, Garima; Mishra, Divya; Oosterhuis, Dorenda; Argemi, Josepmaria; Storm, Gert; Olinga, Peter; Bataller, Ramon; Mohanty, Sujit Kumar; Mishra, Durga Prasad; et al.
Abstract: Non‐alcoholic steatohepatitis (NASH) and alcohol‐associated steatohepatitis (ASH) are the major cause of liver‐related mortality with limited therapeutic options available. In this study, we investigated the role of Src tyrosine kinase in the pathogenesis of (N)ASH. We examined Src kinase expression in livers from patients with NASH, ASH, cirrhosis and biliary atresia, and from preclinical mouse models: methionine choline deficient (MCD)‐diet‐induced NASH, Lieber–DeCarli ethanol (EtOH)‐diet‐induced ASH, carbon tetrachloride (CCl4 )‐ and bile duct ligation (BDL)‐induced liver fibrosis. Functional studies, using Src kinase inhibitor KX2‐391, were performed in NASH and ASH mouse models, and in relevant in vitro models. Transcriptomic analysis revealed increased Src kinase expression in human and mouse diseased livers that positively correlated with disease progression. Src kinase inhibition ameliorated lipid biosynthesis (steatosis); monocytes/macrophages infiltration and inflammatory cytokines expression (inflammation) and hepatic stellate cells (HSCs) activation and collagen expression (fibrosis) in MCD‐diet and EtOH‐diet induced liver disease mouse models. In vitro Src inhibition attenuated FFA‐induced hepatocytic lipid accumulation, LPS/IFNγ‐induced nitric oxide release and expression of several inflammatory signatures in macrophages and TGFβ‐induced HSCs activation, contractility and collagen expression. Moreover, Src inhibition diminished gene expression of inflammatory markers in LPS/IFNγ‐stimulated BMDMs and LPS‐stimulated PCLS, and reduced FA accumulation, macrophage activation and collagen deposition in 3D human liver spheroids. Mechanistic studies further revealed that Src kinase mediated the effects through FAK/PI3K/AKT pathway. Our results demonstrate a multicellular and functional role of Src kinase highlighting Src kinase as a promising therapeutic target in (non)alcoholic steatohepatitis. Abstract : Non‐alcoholic steatohepatitis (NASH) and alcohol‐associated steatohepatitis (ASH) are the major cause of liver‐related mortality with limited therapeutic options available. In this study, we investigated the role of Src tyrosine kinase in the pathogenesis of (N)ASH. Our results demonstrate a multicellular and functional role of Src kinase highlighting Src kinase as a promising therapeutic target in (non)alcoholic steatohepatitis.